2016
DOI: 10.1128/cvi.00696-15
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cell-Mediated Immune Responses to Alternate Booster Schedules of Anthrax Vaccine Adsorbed in Humans

Abstract: A nthrax vaccine adsorbed (AVA; BioThrax; Emergent Bio Solutions Inc., Lansing, MI) is the only Food and Drug Administration (FDA)-approved vaccine in the United States for prevention of anthrax in humans. The primary immunogen in AVA is anthrax toxin protective antigen (PA). Serum anti-PA antibody levels are accurate immune correlates of protection in nonhuman primate (NHP) models of inhalation anthrax and for predicted probability of survival in humans (1-3). There is a significant lack of data in humans reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
1
8
1
Order By: Relevance
“…Although there is evidence that anti-PA antibodies and TNA levels have good correlation in human studies, 7 , 42 , 43 strong correlation was not observed in this study, potentially due to the small sample size. Previous studies have shown that antibody and TNA levels can be highly variable in AVA and AVP vaccinees.…”
Section: Discussioncontrasting
confidence: 78%
“…Although there is evidence that anti-PA antibodies and TNA levels have good correlation in human studies, 7 , 42 , 43 strong correlation was not observed in this study, potentially due to the small sample size. Previous studies have shown that antibody and TNA levels can be highly variable in AVA and AVP vaccinees.…”
Section: Discussioncontrasting
confidence: 78%
“…We next sought to estimate the protection coverage of a vaccine that is capable of eliciting PGT121, PGDM1400 and VRC01. The concentration of the immunoglobulin IgG in human serum is approximately 10 mg/ml, and a serum concentration of 30 μg/ml, which is an approximate titer of 1:300, corresponds to a reasonable sustained vaccine-induced titer achieved via standard immunization protocols 93 . At this concentration, the protection coverage by most bnAbs increases, and if PGT121, PGDM1400 and VRC01 could be elicited at a serum concentration of 30 μg/ml for each Ab, then we project approximately 94% protection coverage (Fig.…”
Section: Bnabs In Prophylaxis Therapy and Vaccine Designmentioning
confidence: 99%
“…Accordingly, we estimate PGT121 would provide 36% protection coverage if it were elicited by vaccination at a serum concentration of 15 μg/ml (on the basis of data for SHIV-SF162P3) and to provide 50% protection coverage if elicited at a concentration of 22 μg/ml (data for SHIV-AD8EO data). We also provide estimated protection coverage if each mAb or combinations of mAbs were elicited at a serum concentration of 30 μg/ml, as a reasonable sustained concentration of Abs elicited by vaccination 93 . In the plot, each symbol represents a unique SHIV isolate (194–200 isolates tested per Ab), with colors (key) indicating the epitope targeted by the Ab (along horizontal axis; SHIV below), and each symbol position represents the neutralization IC 50 in the TZM-bl assay (vertical axis).…”
Section: Fig 1 |mentioning
confidence: 99%
“…It is administered in a series of five doses over 18 months, with a yearly booster after completion. There is evidence that three intramuscular doses are sufficient for protection for up to 3.5 years (27). Studies to evaluate the most effective vaccination schedule are ongoing (27).…”
Section: ………………………………………………………………………………………………mentioning
confidence: 99%
“…There is evidence that three intramuscular doses are sufficient for protection for up to 3.5 years (27). Studies to evaluate the most effective vaccination schedule are ongoing (27). There has been some debate about the safety of the vaccine with reports of chronic adverse effects such as fever, malaise, and joint pain (28).…”
Section: ………………………………………………………………………………………………mentioning
confidence: 99%